Challenges and Opportunities of Teaching English Writing at the Higher Secondary Level in Bangladesh - Rana, Md. Masud; Rashid, Amina; Khalifa, Osama (International Journal of Social Learning (IJSL), 2025)
In Bangladesh, teaching English at the upper secondary level presents a serious challenge and a promising opportunity for educational advancement. The present study examines the complexities of teaching English writing beyond higher secondary education, highlighting the main barriers, and proposes practical recommendations for improvement. Data for this study were retrospectively collected from 120 teachers, students, and parents using a hard-copy survey, digital survey (Google Forms), and in-depth interviews conducted on both face-to-face and online sources. Using the Structural Equation Model (SEM) through Smart PLS 4, the study aimed to test the effectiveness of various teaching methods. The study findings highlight critical factors such as teacher training, curriculum design, and parent-student engagement, even in resource-scarce environments, that support the development of English writing skills. The study also identified the language proficiency gaps and explored how technology-enhanced and interactive teaching methods can improve writing instruction. Based on empirical evidence, this research proposes practical recommendations to overcome the current challenges and facilitate learning outcomes for both educators and students in Bangladesh.